Coastal residential waterways, science and policy-making: The Australian experience. (20th March 2015) - Harvey, Nick; Stocker, Laura
Abstract: Thousands of kilometres of coastal residential waterways have been constructed across the globe, mostly in estuaries. These have caused significant environmental impact demonstrating a need for proper management and planning informed by science. Additional potential impacts of climate change, specifically sea-level rise, make coastal residential waterway developments by their nature particularly vulnerable, with restricted options for adaptation. This paper analyses Australian policies on coastal residential waterways over the last 50 years and the extent to which science, including estuarine and climate change science, has been incorporated into policy decisions or policy formulation. This analysis is in the context of theories on the uptake of science in policy-making and against a background of Australian government and inter-governmental reports indicating the vulnerable nature of low-lying coastal development. This paper reveals that coastal residential waterways referred to as canal estates occur in all Australian mainland states but given the lack of any national coastal policy, the onus is on each individual state to formulate its own policies. These policies are on a continuum from explicit, detailed science-based policy guidelines in some states, through implicit scientific impacts informing political decisions in other states, to generic environmental assessment procedures without specific reference to canal estate development. This paper concludes that the extent to which science has been incorporated into policy-making for canal estates is variable across the Australian states and appears to be heavily influenced by politics. Graphical abstract: Highlights: The five types of Australian canal estates occur mostly in or adjacent to estuaries. Australian canal estates have caused estuarine and coastal environment problems. Science in residential canal estate policy is variable across the Australian states. Public perception and politics are key influences on canal estate policy or bans. Coastal residential waterways have restricted adaptation options for sea-level rise.